L’Ase Negre (1946 - 1949), première revue d’occitanisme politique d’après-guerre - Philippe Canales (Lengas)
Testut coma un ase negre (literally: stubborn like a black mule), Ase Negre, resuming this saying showing the stubbornness of the young post-war occitanists Hélène Cabanes, Léon Cordes and Robert Lafont, is the new political review (that) they launched by being inspired by the magazine Occitania upon which we shall stop as well as on the personality of its founder Charles Camproux. We've got enough letters exchanged during that period to be able to follow the creation of the review. Ase Negre is at first a modest single leaflet issued of the school press of Abeilhan. Soon, the team publishes in August, 46 one 4 pages printed in Olonzac and it surrounds itself with an Editorial committee where appear numerous personalities of the occitanist world. The material and financial difficulties do not prevent the review from proceeding until April-May, 49 after having published 23 numbers; the review had in the meantime taken back the old title Occitania in January, 1948. Ase Negre, having allowed every current of the political occitanism to express himself, contributed to strengthen the unity of the Institute of Occitan Studies arising from politically divergent currents.